PENGARUH EKSTRAK ETANOL DAUN KITOLOD (Isotoma longiflora) TERHADAP VOLUME EDEMA INFLAMASI KRONIS KAKI TIKUS PUTIH MODEL ARTRITIS REUMATOID YANG DIINDUKSI DENGAN COMPLETE FREUNDâS ADJUVANT - , AFIF DANI MARUFAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Rheumatoid arthritis is a degenerative joint disease that involves chronic inflammation of the joints. Drugs of choice to treat rheumatoid arthritis are Non-steroidal Anti-inflammatory Drugs (NSAID) and Disease Modifying Drugs Rheumatoid Arthritis (DMARD). The drugs turned out to have many dangerous side effects. Kitolod plant is a plant known as a medicinal plant. Which the leaves contain alkaloids, flavonoids and saponins believed to have anti-inflammatory effects. Purpose: to determine the anti-inflammatory effects of ethanol extract of kitolod leaves in female rat induced by Complete Freund's Adjuvant (CFA). Methods: This research was a quasi experimental. Thirty female Wistar rats aged 2-3 months with a mean weight of 200 g were divided into 5 treatment groups: distilled water (negative control), methotreksat 0.2 mg / week (positive control), ethanol extract of kitolod leaves 2.02 mg / 200 gr BW, 4.04 mg/200 gr BW, and 8.08 mg/200 gr BW. Female rat injected with CFA 0.1 ml subcutaneously in the left foot to cause rheumatoid arthritis â like edema. Edema volume measurements were performed every three days for six days. On day 6, all were began to receive treatment in accordance with as much as 3 ml per day orally using a sonde, unless methotreksat, given once a week. Treatment is given for 12 days to edema volume measurenment. Results: After 3 days of treatment, the treatment group given methotrexate 0,2 mg / week and ethano extracts of kitolod leaves 8,08 / 200 g BW showed a slight decrease in edema volume compared to the pre-treated, but there is no significant differences (p=0,095). After six day of treatment, no edema voume decreased in all groups. After 12 days of treatment there were aso no reduction in the volume of edema. : Conclusion ethanol extract of kitolod leaves 2.02mg/200 g BW, 4,04 mg/200 g BW gives the percentage volume of smaller edema (190.87% and 172,60%) than in distilled water (214,18%) for 12 days of treatment in reducing chronic inflammatory edema volume of white rat foot as complete Freund's adjuvant (CFA) induced rheumatoid arthritis model.